Youtube social media as an internet resource for records management learning to improve knowledge and job satisfaction - Ismail, Masita; Anuar, Faizul Nizar; Tan, Say Peng; Amir, Zakaria; Razali, Arafat; Maidin, Siti Sarah; Elias, Sofia (Wolters Kluwer - Medknow Publications and Media Pvt. Ltd., 2022)
This article is a concept paper that brings together previous studies that give concepts to the things studied. The aim of this study is to find out the extent to which YouTube can be used as a channel in obtaining information related to Records Information Management by Records Managers other than face-to-face learning methods in the classroom through workshops and courses attended. It is my belief that using the knowledge gained through YouTube as an internet source facilitates Records Managers in performing work in the department more efficiently and smoothly. Next will result in satisfaction in themselves when evaluated high performance by management as well as promotion opportunities. This paper’s argument seeks to highlight values, characteristics, and the importance of knowledge through YouTube media sources as it can be used to solve immediate daily problems in the department and result in employee satisfaction. This study only focuses on the use of social media YouTube-Video recorded by Record Instructors and uploaded to YouTube to be viewed by the public and Record Managers, especially to teach and practice Records Information Management methods in the department. Consequently, it is hoped that it will be able to diversify learning methods, namely online through social media and not only face-to-face in a boring and less effective classroom, in addition to reducing costs and suitable for the Covid-19 situation. We consider YouTube to be an effective tool that can enhance the learning experience if the video is indeed relevant to the subject being studied. It is recommended that instructors integrate YouTube into their respective courses to benefit from the advantages inherent in the context of learning and teaching. The effectiveness of the use of YouTube as a source of information search can be proven in the literature review.